Teacher Candidates’ Knowledge of Special Education Law - Sanders, Pamela (Journal of the American Academy of Special Education Professionals, 2011)
This study sought to assess teacher candidates’ knowledge of special education policies and procedures as mandated by the federal government. It also examines factors associated with accurate knowledge. A sample of 111 teacher candidates, drawn from a Missouri private university, completed a survey. Overall, teacher candidates lacked accurate knowledge and misperceived their lack of knowledge. The most significant predictors of accurate knowledge were completing more special education courses and having positive attitudes toward inclusion. Additionally, this study revealed no differences in knowledge between regular education teacher candidates versus special education teacher candidates.